2015
DOI: 10.1371/journal.pone.0134735
|View full text |Cite
|
Sign up to set email alerts
|

Using DNA Metabarcoding to Identify the Floral Composition of Honey: A New Tool for Investigating Honey Bee Foraging Preferences

Abstract: Identifying the floral composition of honey provides a method for investigating the plants that honey bees visit. We compared melissopalynology, where pollen grains retrieved from honey are identified morphologically, with a DNA metabarcoding approach using the rbcL DNA barcode marker and 454-pyrosequencing. We compared nine honeys supplied by beekeepers in the UK. DNA metabarcoding and melissopalynology were able to detect the most abundant floral components of honey. There was 92% correspondence for the plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
213
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(239 citation statements)
references
References 78 publications
(129 reference statements)
7
213
0
1
Order By: Relevance
“…The usefulness of cox1 for determining phylogenetic relationships among tree topologies were very similar, although support values were generally lower for cox1 (Evans et al, 2007). With agreements to our findings, Hawkins et al, (2015) DNA metabarcoding and melissopalynology were able to detect the most abundant floral components of honey and plant Taxt. There was 92% correspondence for the plant taxa that had an abundance of over 20%.…”
Section: Specific Gene Detection Techniquesupporting
confidence: 90%
“…The usefulness of cox1 for determining phylogenetic relationships among tree topologies were very similar, although support values were generally lower for cox1 (Evans et al, 2007). With agreements to our findings, Hawkins et al, (2015) DNA metabarcoding and melissopalynology were able to detect the most abundant floral components of honey and plant Taxt. There was 92% correspondence for the plant taxa that had an abundance of over 20%.…”
Section: Specific Gene Detection Techniquesupporting
confidence: 90%
“…Following similar observations, suggestions that plastid DNA (ptDNA) was absent from the pollen (e.g., Willerslev et al 2003) may have discouraged early development of pollen DNA barcoding methods. Several studies have now shown proof-of-concept for amplification of ptDNA from pollen (Galimberti et al 2014;Hawkins et al 2015;Kraaijeveld et al 2015;Richardson et al 2015a), so this is no longer considered an issue.…”
Section: Background and Potential Of Pollen Dna Barcodingmentioning
confidence: 99%
“…Another strategy is to use amplicon cloning techniques (e.g., Galimberti et al 2014), but these are also labour-intensive and not comprehensive with respect to sampling depth. Recent improvements and price reductions in high-throughput sequencing (HTS) are promising in terms of addressing the issue of mixed-species identification (i.e., DNA metabarcoding), and recent studies have demonstrated the potential of these methods (Hawkins et al 2015;Keller et al 2015;Kraaijeveld et al 2015;Richardson et al 2015b;Sickel et al 2015). These recent breakthroughs could enable rapid, large-scale species identification of pollen mixtures, with the potential to transform research in a range of fields.…”
Section: Background and Potential Of Pollen Dna Barcodingmentioning
confidence: 99%
“…It is reported that green roofs flowers can provide important habitant and pollen for urban honey bees [71]. Researchers investigated antibacterial medicinal properties of urban honeys [72].…”
Section: Urban Agriculturementioning
confidence: 99%